Evaluation of New Course Proposal Submissions (APCN) by CAPES, year 2019: a study aimed at the enhancement of public policies (Research, Society and Development, 2023)
This work aims to analyze the submission and approval data of the Evaluation of New Course Proposal (APCN) by Coordination of Superior Level Staff Improvement (CAPES) in the year of 2019, proposing actions for the improvement of the evaluation process. To achieve this, descriptive and statistical analyses (Chi-Square test) were conducted, grouping 629 proposals into 14 variables established in this study based on data from CAPES and the Ministry of Education. From these results, 9 standout groups were created, whose approval rates stood out either above or below the global average approval rate (26%) for all submitted proposals. For these standout groups, actions and/or policies were proposed that would either a) reinforce public policies already adopted by CAPES (groups of proposals with approval above the global average) or b) increasing the approval rate (groups of proposals with approval below the global average). Specifically, the standout group 9 focuses on the correlations of APCN with regional disparities in SNPG. Based on the results obtained, it is evident that the analysis of an APCN data can be used to define public policies and improvement actions for subsequent APCNs, thus continually enhancing the evaluation process.